2013
DOI: 10.1167/iovs.13-12104
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Stargardt Disease: Quantitative Assessment of Fundus Autofluorescence, Progression, and Genotype Correlations

Abstract: The AF pattern at baseline influences the enlargement of atrophy over time and has genetic correlates. These data are likely to assist in the provision of counseling on prognosis in Stargardt disease and be valuable for future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
150
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 129 publications
(176 citation statements)
references
References 52 publications
12
150
2
1
Order By: Relevance
“…Decreased FAF is a commonly used marker of retinal degeneration in ABCA4 retinopathy. The estimated rates of enlargement of reduced FAF areas in nullizygous patients (1.4-1.5 mm 2 /y) were comparable with the higher end of the range reported by Chen et al (0.2-2.1 mm 2 /y), 27 the rates reported for similar FAF patterns (0.7-4.4 mm 2 /y), 28 and the rates reported for ERG group 3 (2.3 mm 2 /y), 29 highlighting the utility of this parameter for assessing progressive maculopathy in ABCA4-retinopathy. The estimated rates of progression for p.G1961E patients were significantly slower (0.03-0.06 mm 2 /y), highlighting the importance of considering the genotype in future clinical studies, especially involving patients with otherwise overlapping characteristics (e.g., early disease onset).…”
Section: Discussionsupporting
confidence: 88%
“…Decreased FAF is a commonly used marker of retinal degeneration in ABCA4 retinopathy. The estimated rates of enlargement of reduced FAF areas in nullizygous patients (1.4-1.5 mm 2 /y) were comparable with the higher end of the range reported by Chen et al (0.2-2.1 mm 2 /y), 27 the rates reported for similar FAF patterns (0.7-4.4 mm 2 /y), 28 and the rates reported for ERG group 3 (2.3 mm 2 /y), 29 highlighting the utility of this parameter for assessing progressive maculopathy in ABCA4-retinopathy. The estimated rates of progression for p.G1961E patients were significantly slower (0.03-0.06 mm 2 /y), highlighting the importance of considering the genotype in future clinical studies, especially involving patients with otherwise overlapping characteristics (e.g., early disease onset).…”
Section: Discussionsupporting
confidence: 88%
“…He reported that some cases also had macular degeneration [2,3]. Stargardt's disease and fundus flavimaculatus usually have an autosomal recessive inheritance pattern [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16] and rarely an autosomal dominant pattern [17]. …”
Section: Introductionmentioning
confidence: 99%
“…ABCA4 transports N-retinylidene-PE to the cytosolic leaflet of the cell membrane, where it dissociates into ATR and PE. ATR within the RPE cell is reduced to all-trans retinol by retinol dehydrogenase, the latter entering the visual cycle for conversion to 11-cis retinal (12). When ABCA4 is mutated, transport is compromised, allowing for the accumulation of ATR within the disc lumens and gradually creating diretinoid-pyridinum-eithanolamine (A2E) and -retinal dimer (RALdi).…”
mentioning
confidence: 99%